1991
DOI: 10.1099/00207713-41-2-229
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma spermatophilum, a New Species Isolated from Human Spermatozoa and Cervix

Abstract: A mycoplasma isolated from human spermatozoa and a human cervix was shown to be serologically distinct from 98 previously recognized MycopEasma and AchoZepZasma spp. Six mycoplasma colonies were cloned and examined in detail for morphology, growth, and biochemical characteristics; five of these were from sperm samples and one was from a cervix. These strains were closely related and had the following properties: guanine-plus-cytosine content of 32 mol% , requirement for sterol, and anaerobic growth. Glucose wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
1
4
0
2
Order By: Relevance
“…Some investigators did not show any significant correlation between M. hominis infection and semen quality [36] [37]. Statistically, the present study did not show any significant difference between sperm count, motility and/or morphology [38] [39]. Previous studies have reported that the presence of mycoplasmas in sperm specimens has no real effect on the semen quality, nor on the leukocyte count as reported by Andrade-Rocha [26] [40].…”
Section: Discussionsupporting
confidence: 44%
“…Some investigators did not show any significant correlation between M. hominis infection and semen quality [36] [37]. Statistically, the present study did not show any significant difference between sperm count, motility and/or morphology [38] [39]. Previous studies have reported that the presence of mycoplasmas in sperm specimens has no real effect on the semen quality, nor on the leukocyte count as reported by Andrade-Rocha [26] [40].…”
Section: Discussionsupporting
confidence: 44%
“…are less common (5,14,35,37). The frequency of isolation of urogenital mycoplasmas depends in part on the group of individuals studied.…”
mentioning
confidence: 99%
“…Several mycoplasma species have been isolated from respiratory and genital tracts of humans (10). Recently, a fastidious mycoplasma was isolated from urogenital tracts of patients with infertility problems and named Mycoplasma spermatophilum (3,4). Mycoplasma primatum, a species commonly present in nonhuman primates, has been isolated from human urinary tract as well (4, 1 1, 12).…”
mentioning
confidence: 99%